The use of literacy approach to teach writing of descriptive text at the seventh grade students Of SMPN 1 Ngebel - Yuliani, Tanti (Universitas PGRI Madiun, 2017)
The main purpose of teaching learning English in Junior High School to develop the students? competence and knowledge in four language skills, Speaking, Reading, Listening and Writing. One of the difficult skills is writing. In this research are describe how are the uses, problems, and solutions of the use of Literacy Approach to Teach Writing of Descriptive Text At The Seventh Grade Students of SMPN 1 Ngebel in Schooling Years 2013/2014. Literacy approach is one of the approaches used to teach writing especially in descriptive text because Literacy approach is the ability to read and write. There are some step of teaching writing, they are planning, composing, and revising. This research uses descriptive qualitative research. Participant/Informant of the research are the English teacher and the seventh grade students of SMPN I Ngebel Ponorogo. This research uses purposive sampling technique. The techniques which are used to collect the data are observation, interview, and documentation. Techniques of the data analysis are data reduction, data display and drawing conclusions. The result of the analyzing data indicates that the uses of literacy approach in teaching writing of descriptive text are divided into two steps. The first is preparation steps and the second is learning process. The learning process uses literacy approach includes introduce and giving explanation the descriptive text, give the modal of the descriptive text and have text to analyze, make group work to discussion the students? ideas, give the chance to make students? own product and also checking the students? understanding about the material. Besides, the problem of the use literacy approach in writing of descriptive text are sometimes the students are noisy in the classroom and their vocabulary are still low. The students feel afraid to deliver their opinion and ideas in teaching and learning process. The solution of the use literacy approach in writing of descriptive are the students must make group work of the students? worksheet, Teacher controls the students and gives scores for students.